Compensation in the public sector in Bangladesh: trends,adequacy and equity - Chowdhury, Md Emdadul Hoq (BRAC University, 2010)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Governance and Development, 2006.